2003
DOI: 10.1016/s0377-1237(03)80142-9
|View full text |Cite
|
Sign up to set email alerts
|

Conventional B-mode Ultrasonography for Evaluation of Retinal Disorders

Abstract: Sonographic study of 164 patients (328 eyes) in the present series highlights the advantages of ocular ultra sonography (B-mode) in the evaluation of retinal disorders especially in patients with opaque ocular media. B-mode sonography of the eye is a rapid, cheap, safe and reliable investigation for the eye. The sensitivity and specificity of this modality in detecting ocular pathologies has been recorded as extremely high and is of great value to the eye surgeon for a preoperative assessment of the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…We could not demonstrate any retinal detachment associated with the tumor. Similar results were shown by Sen et al study where retinoblastoma formed 3% of various ocular abnormalities [10] .…”
Section: Disscussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We could not demonstrate any retinal detachment associated with the tumor. Similar results were shown by Sen et al study where retinoblastoma formed 3% of various ocular abnormalities [10] .…”
Section: Disscussionsupporting
confidence: 89%
“…Sen et al showed an incidence of 21.34% (34 out of 164 cases examined) due to traumatic and non-traumatic causes [10] . Study by Sharma demonstrated 26 cases (21.31%) of retinal detachment diagnosed out of 122 cases scanned [11] .…”
Section: Disscussionmentioning
confidence: 99%
“…Ultrasonography is essential when visualization of posterior eye segment structures is difficult. These conditions include lid problems (severe edema, tarsorrhaphy), keratoprosthesis, corneal opacities (scars, severe edema), hypopyon, hyphema, different papillary membranes, refractory miosis, dense cataracts and various vitreous opacities (hemorrhage, inflammatory debris) (7,8,9,10). Ultrasonography is used for diagnostic purposes when ocular pathology is clinically visible, while it can accurately image and measure intraocular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the eye and orbit is facilitated by the use of the high frequency sound (8)(9)(10) MHz, 20 MHz, and 50-100 MHz) (1). First use of ultrasound in ophthalmology was in 1956. by Mundt and Hughes who used A-scan mode to evaluate an intraocular tumor (2), while Baum and Greenwood were first to introduce B-scan into the ophthalmol-ogy (3).…”
Section: Introductionmentioning
confidence: 99%
“…Sonography is used more commonly by ophthalmologists to evaluate the eye, particularly when direct examination by slit-lamp and funduscopy is not sufficient. Detailed cross-sectional anatomy of the entire globe is possible with conventional sonographic equipment [1][2][3][4]; anterior chamber visualization requires a dedicated sonographic biomicroscope [5]. Color Doppler and A-mode sonography [1,6] are reported to be useful in characterizing masses.…”
mentioning
confidence: 99%